Steinernema taiwanensis n. sp. (Rhabditida: Steinernematidae), a new entomopathogenic nematode from Taiwan - Tseng, Ching-Tzu; Hou, Roger F.; Tang, Li-Cheng (Zootaxa, 2018)
A new isolate of the entomopathogenic nematode, Steinernema taiwanensis n. sp., was isolated from soil in Pingtung County, Taiwan. This new species could be characterized and distinguished from other related species by its morphological characters, morphometrics, and phylogenetic analysis. The body length and distance from anterior end to nerve ring of infective juveniles is 1012 (983–1045) µm and 124 (120–127) µm, lateral field formula 2, 6, 7, 8, 2, and the tail length 90 (79–96) µm without dorsal constriction in tail region. The first generation males of S. taiwanensis n. sp. are characterized by spicule shape, smooth blade tip, 23 genital papillae (11 pairs and 1 single papilla), spicule length of 94 (89–99) µm and gubernaculum length of 68 (65–70) µm. Females from the first generation of S. taiwanensis n. sp. have no epiptygmata and a slightly developed post-anal swelling. Phylogenetic analysis of ITS and D2D3 regions of rDNA showed that S. taiwanensis n. sp. belongs to the Longicaudum-clade and comprises a monophyletic group with S. guangdongense and S. longicaudum. The new isolate is described as a novel species according to morphological and phylogenetic analyses.